Mastering all genres: Exploring Ninth Grade Students' Text Comprehension Skills Through Google Forms - Hendra Putra; Indra Indra; M Ridha; Reski Hasan (FKIP - Universitas Tanjungpura, 2023)
Understanding what one reads is a significant component of the reading journey. To effectively engage with different types of texts, students must possess strong reading comprehension skills. The goal of this study is to figure out how well kids can understand various forms of literature. Descriptive, recount, report, narrative, and procedural texts are examples of different types of texts. In this research, a quantitative method is utilized to perform data calculations. Reading assessments are incorporated as a tool in this process. The assessments consist of 25 questions and offer a selection of five text types: descriptive, recount, report, narrative, and procedure texts. The findings indicate that students have demonstrated a 50 percent proficiency in comprehending different text types, which suggests a relatively low level of overall comprehension. However, there is a positive trend observed in the children's understanding of descriptive language.